GAMIFICATION TECHNIQUES IN TEACHING UZBEK VOCABULARY AND GRAMMAR - Salisheva Zilola Ismailovna (European Science Publishing, 2025)
This article explores the application of gamification techniques in teaching Uzbek vocabulary and grammar, emphasizing their pedagogical potential in enhancing language acquisition. Gamification involves the use of game design elements in non-game contexts to improve learner engagement, motivation, and outcomes. In the context of Uzbek language instruction, particularly among foreign learners and university students in Uzbekistan, gamified learning environments offer innovative pathways to address traditional challenges in vocabulary retention and grammatical understanding. This study investigates both digital and classroom-based gamification strategies, analyzing their effects on learner performance, motivation, and long-term linguistic competence. Drawing upon relevant theoretical frameworks and practical implementations, the paper aims to provide a systematic evaluation of gamification’s role in modernizing Uzbek language education.
Keywords: Uzbek language, gamification, language learning, vocabulary acquisition, grammar instruction, educational technology, motivation, engagement, philological education, higher education.